FACTORS ASSOCIATED WITH THE UTILIZATION OF PUBLIC HEALTH CENTER IN CENTRAL JAVA - Marizka Khairunnisa; Agung Dwi Laksono; Sidiq Purwoko; Sri Sulasmi; Afi Nursafingi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Background: The Public Health Center (PHC) is a gatekeeper to formal healthcare in Indonesia. PHCs in Central Java have met the basic health facility readiness standard, but there are still numerous challenges to increasing the utilization of PHCs. Aims: This study aimed to analyze the factors related to the utilization of PHC in Central Java. Methods: This cross-sectional study used secondary data from the 2018 Indonesia Basic Health Research, with 63,118 total samples. The independent variables were residence, age, gender, marital status, education, insurance, and socioeconomic, while the dependent variable was the utilization of PHC. The data were analyzed using a binary logistic regression. Results: The average rate of utilization of PHC in Central Java in 2018 was 5.7%. Those aged 46-65 and >65 years old, women, married and widowers, and those with health insurance had a higher possibility of utilizing PHC. Meanwhile, those who graduated from secondary and tertiary school, the employed, and the wealthiest group had a lower possibility of utilizing PHC. Conclusion: The factors related to the utilization of PHC in Central Java are age group, gender, marital status, education level, working status, health insurance ownership, and socioeconomic status. Keywords: basic health service, health service access, public health, public health center